Corporate debt policy of Malaysian SMEs: empirical evidence from firm dynamic panel data - Lin, Woon Leong; Yip, Nick; Sambasivan, Murali; Ho, Jo Ann (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
Financing has been identified as a dominant constraint to Malaysian small and medium-sized enterprises (SMEs). Yet, limited attention has been given to the challenges faced by the SMEs in financing their operations. This paper investigates the determinants of capital structure and use of financing for Malaysian SMEs in manufacturing sector and examines hypotheses by utilising a static trade-off choice or pecking order framework by employing a series of firm characteristics including: size, age, asset structure, profitability, growth, taxation and risk. The system Generalised Method of Moment (GMM) approach has been used for the estimation. The findings suggest that most of the determinants of capital structure presented by the theory of finance appear to be relevant for the Malaysian SMEs. Firm size and asset structure have a significantly positive effect on the leverage ratio in SMEs, while age and taxation have a negative effect. Though, growth has an impact on the total debt of the firms, profitability and risk does not have any significant effect on the decision of debt decision making in Malaysian SMEs. Furthermore, the findings of the study show that Malaysian SMEs in the manufacturing sector generally operate based on a combination of the pecking order and the trade-off theory while borrowing in the long-term and short-term.